1987
DOI: 10.1007/bf00314139
|View full text |Cite
|
Sign up to set email alerts
|

Multiple subcortical haemorrhages following lumbar metrizamide myelography

Abstract: The case is presented of a patient showing multiple subcortical haemorrhages after lumbar metrizamide myelography. This complication after intrathecally administered metrizamide contrast medium appears not to have been reported before. Several different possible explanations are proposed for the phenomena observed in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[4][5][6][7][8] At present, the most likely explanation for the onset of this complication is a sudden variation in cerebral blood flow as a consequence of cerebral decompression. [6][7][8]12,13 Indeed, intracerebral haemorrhage owing to a variation of the intracranial pressure gradient, has been reported even after lumbar puncture for myelography [15][16][17] or spinal analgesia, 18,19 after evacuation of an extracerebral fluid collection; 8 in other cases, it occurred postoperatively far from the site of craniotomy. [20][21][22] SPECT studies have demonstrated that cerebral blood flow in patients with chronic subdural haematoma is diminished, particularly in the homolateral basal ganglia and thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] At present, the most likely explanation for the onset of this complication is a sudden variation in cerebral blood flow as a consequence of cerebral decompression. [6][7][8]12,13 Indeed, intracerebral haemorrhage owing to a variation of the intracranial pressure gradient, has been reported even after lumbar puncture for myelography [15][16][17] or spinal analgesia, 18,19 after evacuation of an extracerebral fluid collection; 8 in other cases, it occurred postoperatively far from the site of craniotomy. [20][21][22] SPECT studies have demonstrated that cerebral blood flow in patients with chronic subdural haematoma is diminished, particularly in the homolateral basal ganglia and thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases of intracerebral haemorrhage following dural tap are related to lumbar myelography [7][8][9][10] , which usually involves 20 or 21 gauge needles. Most of these cases presented with headache and the initial diagnosis was PDPH.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication is post dural puncture headache 1,2 , and less commonly subdural haematoma [3][4][5][6] . Intracerebral haemorrhage appears rare 1,[7][8][9][10][11] . We report a case of bilateral frontal haemorrhages following continuous spinal postoperative analgesia, an event not previously described in the literature.…”
mentioning
confidence: 99%